Targeting extracellular matrix stiffness for cancer therapy - Feng, Xiuqin; Cao, Fujun; Wu, Xiangji; Xie, Wenyan; Wang, Ping; Jiang, Hong (Frontiers in Immunology, 2024)
The physical characteristics of the tumor microenvironment (TME) include solid stress, interstitial fluid pressure, tissue stiffness and microarchitecture. Among them, abnormal changes in tissue stiffness hinder drug delivery, inhibit infiltration of immune killer cells to the tumor site, and contribute to tumor resistance to immunotherapy. Therefore, targeting tissue stiffness to increase the infiltration of drugs and immune cells can offer a powerful support and opportunities to improve the immunotherapy efficacy in solid tumors. In this review, we discuss the mechanical properties of tumors, the impact of a stiff TME on tumor cells and immune cells, and the strategies to modulate tumor mechanics.